CONCEPTUAL APPROACH TO THE DEVELOPMENT OF UX DESIGN FOR A UNIVERSITY MOBILE APPLICATION: PERSONAS AND USER JOURNEYS - Кутельмах, Роман (SWorldJournal, 2025)
A persistent challenge in contemporary higher education is the effectiveness of student–lecturer interaction. Students aspire to deepen their knowledge by means of modern learning modalities, while lecturers aim to deliver instruction with maximum efficie